CARDIOVASCULAR OUTCOMES AT RECOMMENDED BLOOD PRESSURE TARGETS IN MIDDLE AGED AND ELDERLY PATIENTS WITH TYPE 2 DIABETES MELLITUS AND HYPERTENSION. (April 2021) - Olsen, Eirik; Holzhauer, Björn; Julius, Stevo; Kjeldsen, Sverre; Larstorp, Anne; Mancia, Giuseppe; Mehlum, Maria; Mo, Rune; Rostrup, Morten; Søraas, Camilla; Zappe, Dion; Weber, Michael
Abstract : Objective: The optimal blood pressure (BP) target for patients with type-2 diabetes mellitus (DM) and hypertension has been set at < 130/80 mmHg in guidelines. However, available data of event-based clinical outcomes trials show that little evidence supports these guideline recommendations. Figure. No caption available. Design and method: We addressed this issue by post-hoc analyzing the risk of cardiovascular (CV) events in mostly elderly high-risk hypertensive patients with type-2 DM participating in the Valsartan Antihypertensive Long-term Use Evaluation (VALUE) trial. Patients (n = 5250) were divided into 4 groups according to the proportion of on-treatment visits before the occurrence of an event (< 25%, 25%-49%, 50–74%, 75% -100%) in which BP was reduced to < 140/90 or < 130/80 mmHg. Results: After adjustment for baseline demographic differences between groups, a reduction in the proportion of visits in which BP achieved < 140/90 mmHg accompanied a progressive increase in the risk of CV mortality and morbidity as well as of cause-specific events such as stroke, myocardial infarction and heart failure (Figure, upper panel). A progressive reduction in the proportion of visits in which BP was reduced < 130/80 mmHg did not have any effect on CV risks (Figure, lower panel). Conclusions: In mostly elderly high-risk hypertensive patients with type-2 diabetes mellitus participating in the VALUE trial, achieving more frequently BP < 140/90 mmHg showed a marked protective effect on overall and all cause specific cardiovascular outcomes. This was not the case for a more frequent achievement of the more intensive BP target, i.e. < 130/80 mmHg.